Genetic markers for disease monitoring using the SWEET kit - CGIAR Research Program on Rice (2021)
Any national program, private sector, or research institution in Asia or Africa has access to the disease monitoring platform created by IRRI. The platform is validated and can be used anytime. Users only have to submit disease leaf samples.